Contributions of nature-based solutions to reducing people’s vulnerabilities to climate change across the rural Global South - Stephen Woroniecki; Femke A. Spiegelenberg; Alexandre Chausson; Beth Turner; Isabel Key; Haseeb Md. Irfanullah; Nathalie Seddon (Climate and Development, 2023)

Getting the message right on nature‐based solutions to climate change - Nathalie Seddon; Alison Smith; Pete Smith; Isabel Key; Alexandre Chausson; Cécile Girardin; Jo House; Shilpi Srivastava; Beth Turner (Global Change Biology, 2021)
Nature‐based solutions (NbS)—solutions to societal challenges that involve working with nature—have recently gained popularity as an integrated approach that can address climate change and biodiversity loss, while supporting sustainable development. Although well‐designed NbS can deliver multiple benefits for people and nature, much of the recent limelight has been on tree planting for carbon sequestration. There are serious concerns that this is distracting from the need to rapidly phase out use of fossil fuels and protect existing intact ecosystems. There are also concerns that the expansion of forestry framed as a climate change mitigation solution is coming at the cost of carbon rich and biodiverse native ecosystems and local resource rights. Here, we discuss the promise and pitfalls of the NbS framing and its current political traction, and we present recommendations on how to get the message right. We urge policymakers, practitioners and researchers to consider the synergies and trade‐offs associated with NbS and to follow four guiding principles to enable NbS to provide sustainable benefits to society: (1) NbS are not a substitute for the rapid phase out of fossil fuels; (2) NbS involve a wide range of ecosystems on land and in the sea, not just forests; (3) NbS are implemented with the full engagement and consent of Indigenous Peoples and local communities in a way that respects their cultural and ecological rights; and (4) NbS should be explicitly designed to provide measurable benefits for biodiversity. Only by following these guidelines will we design robust and resilient NbS that address the urgent challenges of climate change and biodiversity loss, sustaining nature and people together, now and into the future.

Mapping the effectiveness of nature‐based solutions for climate change adaptation - Alexandre Chausson; Beth Turner; Dan Seddon; Nicole Chabaneix; Cécile A. J. Girardin; Valerie Kapos; Isabel Key; Dilys Roe; Alison Smith; Stephen Woroniecki; Nathalie Seddon (Global Change Biology, 2020)
Nature‐based solutions (NbS) to climate change currently have considerable political traction. However, national intentions to deploy NbS have yet to be fully translated into evidence‐based targets and action on the ground. To enable NbS policy and practice to be better informed by science, we produced the first global systematic map of evidence on the effectiveness of nature‐based interventions for addressing the impacts of climate change and hydrometeorological hazards on people. Most of the interventions in natural or semi‐natural ecosystems were reported to have ameliorated adverse climate impacts. Conversely, interventions involving created ecosystems (e.g., afforestation) were associated with trade‐offs; such studies primarily reported reduced soil erosion or increased vegetation cover but lower water availability, although this evidence was geographically restricted. Overall, studies reported more synergies than trade‐offs between reduced climate impacts and broader ecological, social, and climate change mitigation outcomes. In addition, nature‐based interventions were most often shown to be as effective or more so than alternative interventions for addressing climate impacts. However, there were substantial gaps in the evidence base. Notably, there were few studies of the cost‐effectiveness of interventions compared to alternatives and few integrated assessments considering broader social and ecological outcomes. There was also a bias in evidence toward the Global North, despite communities in the Global South being generally more vulnerable to climate impacts. To build resilience to climate change worldwide, it is imperative that we protect and harness the benefits that nature can provide, which can only be done effectively if informed by a strengthened evidence base.

Barn Owl (Tyto alba) breeding biology in relation to breeding season climate - Alexandre Chausson; Isabelle Henry; Bettina Almasi; Alexandre Roulin (Journal of Ornithology, 2014)